2020
DOI: 10.1186/s12879-020-05278-y
|View full text |Cite|
|
Sign up to set email alerts
|

Bioaerosol sampling of patients with suspected pulmonary tuberculosis: a study protocol

Abstract: Background: Tuberculosis (TB) is transmitted in bioaerosols containing Mycobacterium tuberculosis (Mtb). Despite being central to ongoing TB transmission, no routine diagnostic assay exists to measure Mtb in bioaerosols. Furthermore, published studies of Mtb in bioaerosol samples have been limited to individuals with sputum-positive pulmonary TB. Notably, TB diagnosis is based on clinical symptoms and sputum laboratory findings. This is despite the fact that approximately half of all patients commencing TB tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…(ii) The bacillary counts and morphological phenotypes presented here are not augmented with clinical metadata (chest radiography scores, HIV status, etc.). Our intention in this study was to establish the technological platform for bioaerosol sample capture and analysis-as described in our recently published protocol [34], current and planned work involves the application of the RASC to carefully designed clinical cohorts. (iii) The criteria used to classify DMN-tre + organisms as "putative Mtb" are potentially restrictive, especially given that prevailing assumptions about the size and shape of clinical Mtb isolates are heavily influenced by the commonly applied staining methods (almost never supported by confirmatory molecular or microbiological data) as well as knowledge of Mtb morphology from growth in vitro in defined culture, in some cases in intracellular infection models or under applied stress conditions.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…(ii) The bacillary counts and morphological phenotypes presented here are not augmented with clinical metadata (chest radiography scores, HIV status, etc.). Our intention in this study was to establish the technological platform for bioaerosol sample capture and analysis-as described in our recently published protocol [34], current and planned work involves the application of the RASC to carefully designed clinical cohorts. (iii) The criteria used to classify DMN-tre + organisms as "putative Mtb" are potentially restrictive, especially given that prevailing assumptions about the size and shape of clinical Mtb isolates are heavily influenced by the commonly applied staining methods (almost never supported by confirmatory molecular or microbiological data) as well as knowledge of Mtb morphology from growth in vitro in defined culture, in some cases in intracellular infection models or under applied stress conditions.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…7 The mixture contained in breath is not as complicated as those in sputum, serum and urine, and can be used for screening, early auxiliary diagnosis and disease monitoring of TB. 8,9 It has been confirmed that there is cultivable MTB in the exhaled breath of TB patients and it is feasible and reproducible to collect exhaled breath for detection. 10 Collecting exhaled breath condensate (EBC) is a common method for exhaled breath sample collection.…”
Section: Introductionmentioning
confidence: 92%
“…because it does not have to be delivered by medical professionals. In a sampling bag, users blow in and set the BAP with a breath-filled sampling bag and a disposable unit containing the purpose of biological detection of particulates by aerosol [8]. The BAP sample pack collection and the system detect all bioaerosol particles immediately in the sampling bag and indicates whether the patient's disease is favorable or not.…”
Section: Concept Of Detecting Biological Aerosol Particles In a Patient's Breathmentioning
confidence: 99%